Good question!

X = unknown number

x/3 -2 = x/4

Get rid of the denominators

1st, the 3

3 * x/3 -2 = x/4

x - 6 = 3x/4

then get rid of the 4

4x - 24 = 3x

x - 24 = 0

x = 24

Proof: 24/3 -2 = 24/4

24/3 = 8

8 minus 2 = 6

24/4 = 6

6 = 6 Hope this helps

X = unknown number

x/3 -2 = x/4

Get rid of the denominators

1st, the 3

3 * x/3 -2 = x/4

x - 6 = 3x/4

then get rid of the 4

4x - 24 = 3x

x - 24 = 0

x = 24

Proof: 24/3 -2 = 24/4

24/3 = 8

8 minus 2 = 6

24/4 = 6

6 = 6 Hope this helps